Gending Sriwijaya Dance Training For Bipa Students At Thammasat University Thailand - Triana, Dinny Devi; Oktarini, Selly; Soewardjo, Kristiono; Nisa, Putri Faridatun (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2023)
This Community Service activity aims to introduce Indonesian culture, especially those that have similarities to traditional Thai dances. The dance that was introduced and taught in this activity was the Gending Sriwijaya dance which originates from Palembang. Dance material is given in the BIPA class at the Faculty of Liberal Arts, University of Thailand. The training method is carried out in two ways, the first is online with additional video tutorials, for 5x meetings, then it is carried out offline for 2x face-to-face. Methods the training method uses modifications developed by Louis Genci (1966), Otto and Glaser (1970), namely 1) analyzing the initial abilities of the trainees, 2) formulating objectives, 3) determining methods and media that suit the characteristics of the trainees, 4) demonstrating and practicing skills, 5) evaluating training results. This method is very relevant to use as a long-distance dance training strategy involving foreign students. The success of this activity can be seen from the results of the questionnaire, where 90% of students were happy and wanted to learn other Indonesian dances. At the end of the training, there was a performance featuring 8 Thai students who focused on learning the Sriwijawa Gending Dance.